Peran Administrasi Kurikulum dalam Peningkatan Kualitas Pendidikan: Tinjauan Tugas Guru pada Implementasi Kurikulum - Fatimah, Meti; Tisnawati, Tin; Soleha, Zachro (Lembaga Yasin AlSys, 2024)
The curriculum is the core of the educational system, guiding the objectives, targets, and learning processes in schools. Effective curriculum administration is essential to ensure successful educational outcomes by managing the planning, implementation, and evaluation processes. This study aims to explore the strategies and challenges involved in curriculum administration in schools. Utilizing a literature review method, this research analyzes primary and secondary sources from relevant literature on curriculum management in education. The findings indicate that a well-structured curriculum administration can enhance teaching quality and student performance. However, challenges such as resource limitations, policy misalignment, and lack of flexibility in curriculum design continue to impede the process. This study recommends improving collaboration between educators and administrators, integrating technological advancements, and ensuring curriculum relevance to student needs and global demands. By addressing these challenges, curriculum administration can play a critical role in achieving quality education and preparing students to face modern global challenges.